Effects of Allicin on Hypertension and Cardiac Function in Chronic Kidney Disease - García-Trejo, Ehécatl M. A.; Arellano-Buendía, Abraham S.; Argüello-García, Raúl; Loredo Mendoza, María Lilia; García-Arroyo, Fernando E.; Arellano-Mendoza, Mónica G.; Castillo-Hernández, María C.; Guevara-Balcázar, Gustavo; Tapia, Edilia; Sánchez-Lozada, Laura Gabriela; Osorio-Alonso, Horacio (My University, 2016)
This work was performed to study the effect of allicin on hypertension and cardiac function in a rat model of CKD. The groups were control, CKD (5/6 nephrectomy), and CKD-allicin treated (CKDA) (40 mg/kg day/p.o.). Blood pressure was monitored (weekly/6 weeks). The cardiac function, vascular response to angiotensin II, oxidative stress, and heart morphometric parameters were determined. The CKD group showed hypertension and proteinuria. The coronary perfusion and left ventricular pressures were decreased in CKD group. In contrast, the vascular response to angiotensin II and expression of angiotensin II type 1 receptor (AT1R) were increased. These data were associated with the increment in morphometric parameters (weight of heart and left ventricle, heart/BW and left ventricular mass index, and wall thickness). Concurrently, the oxidative stress was increased and correlated inversely with the expression of Nrf2, Keap1, and antioxidant enzymes Nrf2-regulated. Allicin treatment attenuated hypertension and improved the renal and the cardiac dysfunctions; furthermore, it decreased the vascular reactivity to angiotensin II, AT1R overexpression, and preserved morphometric parameters. Allicin also downregulated Keap1 and increased Nrf2 expression, upregulated the antioxidant enzymes, and reduced oxidative stress. In conclusion, allicin showed an antihypertensive, nephroprotective, cardioprotective, and antioxidant effects, likely through downregulation of AT1R and Keap1 expression. © 2016 Ehécatl M. A. García-Trejo et al.